Anticipatory postural adjustments and kinematic analysis of step ascent and descent in adults with Down syndrome. Issue 5 (20th February 2023) - Ferrario, C.; Condoluci, C.; Tarabini, M.; Manzia, C. M.; Galli, M.
Abstract: Background: Step ascent and descent is one of the most common daily tasks. Although it is generally considered a rather simple movement, it may not be so easy for participants with Down syndrome. Methods: A kinematic analysis of step ascent and descent was conducted, and a comparison between 11 adult participants with Down syndrome and 23 healthy participants was carried out. This analysis was accompanied by a posturographic analysis with the aim of evaluating aspects relating to balance. The principal aim of postural control was to investigate the trajectory of the centre of pressure, while the kinematic analysis of movement included the following: (1) the analysis of anticipatory postural adjustments, (2) the calculation of spatiotemporal parameters and (3) the evaluation of articular range of motion. Results: A general instability for participants with Down syndrome, highlighted in the postural control by an increased anteroposterior and mediolateral excursion, when the test was conducted with both open and closed eyes, was found out. Regarding anticipatory postural adjustments, this deficit in balance control was revealed by the execution of small steps before completing the movement and by a much longer preparation time anticipating the movement. In addition, the kinematic analysis reported a longer ascent and descent time and a lower velocity, accompanied by a greater rising of both limbs in ascent, which indicates an increased perception of the obstacle. Finally, a wider trunk range of motion in both the sagittal and frontal planes was revealed. Conclusions: All the data confirm a compromised balance control that could be associated with damage to the sensorimotor centre.